The provision of childcare services. A comparative review of 30 European countries (Luxembourg, 2009)
"The availability of adequate childcare services is a growing concern for citizens across Europe. A better availability of childcare services can boost labour market participation and support gender equality and social inclusion while also working to reverse declining fertility rates by reducing the cost of childbearing in terms of career opportunities. This report examines the situation of childcare across 30 European countries including the extent to which demand is met, quality and affordability of services and the national childcare policies. "